DEVELOPING READING MATERIALS TO IMPROVE THE LEARNERS' COMPREHENSION OF SDGs CONCEPTS - Kristining Seva; Asnita Sirait; Tutik Rachmawati (PROJECT (Professional Journal of English Education), 2023)
Materials for the public administration department must be updated to address challenges connected to the SDGs.The previous research findings portrayed the student's preferences in strengthening their reading abilities in SDGs contents, which is the first emphasis of this research; the second is the absence of specific English for Specific Material (ESP) reading material related to SDGs. Using action research, the phases of analyzing, exploring, designing, constructing, and evaluating will be anchored in this study, resulting in suggested reading texts with learning activities and exercises illustrated in lesson plans. The study's participants are students who have completed 60% of their classes. The findings of this study will also be assessed by substance and language specialists in order to validate and gain input for necessary adjustments to suggested reading materials and activities. The findings show 30.5% of students said materials regarding SDGs issues are extremely important, and 58.5% said it is essential to include them in their reading text to enhance their English. With 90% on the 'agree' scale, the expert judgment results support the applicability of the materials and activities designed. This demonstrates that the materials and activities designed are appropriate for the students in order to improve their reading skills.